2018
DOI: 10.1063/1.5020333
|View full text |Cite|
|
Sign up to set email alerts
|

A closed-form analytical model for predicting 3D boundary layer displacement thickness for the validation of viscous flow solvers

Abstract: A closed-form analytical model is developed for estimating the 3D boundary-layer-displacement thickness of an internal flow system at the Sanal flow choking condition for adiabatic flows obeying the physics of compressible viscous fluids. At this unique condition the boundary-layer blockage induced fluid-throat choking and the adiabatic wall-friction persuaded flow choking occur at a single sonic-fluid-throat location. The beauty and novelty of this model is that without missing the flow physics we could predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(127 citation statements)
references
References 32 publications
2
121
0
Order By: Relevance
“…Therefore, a priori knowledge of the HCR of the evolved gas is essential for predicting the occurrence of Fanno flow choking, Rayleigh flow choking, and Sanal flow choking conditions in any wall-bounded fluid flow system. Authors [1,[5][6][7][8][9][10] reported that at the LCHI, the blood vessel with bifurcation and without any plaque and stent could experience the Sanal flow choking due to the blockage factor ( Figure 2f) leading to asymptomatic hemorrhage/stroke as a consequence of the transient pressure overshoot as a result of the shock wave generation. [6] The research findings of the authors corroborated that, [1,6] at the Sanal flow choking condition, when the BPR reaches the LCHI anywhere in the circulatory circuit with sudden expansion or bifurcation region the chances of the physical occurrence of cavitation and shock waves are very high because of the off-designed CD nozzle-shaped-channel flow in blood vessels.…”
Section: Backgroundsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, a priori knowledge of the HCR of the evolved gas is essential for predicting the occurrence of Fanno flow choking, Rayleigh flow choking, and Sanal flow choking conditions in any wall-bounded fluid flow system. Authors [1,[5][6][7][8][9][10] reported that at the LCHI, the blood vessel with bifurcation and without any plaque and stent could experience the Sanal flow choking due to the blockage factor ( Figure 2f) leading to asymptomatic hemorrhage/stroke as a consequence of the transient pressure overshoot as a result of the shock wave generation. [6] The research findings of the authors corroborated that, [1,6] at the Sanal flow choking condition, when the BPR reaches the LCHI anywhere in the circulatory circuit with sudden expansion or bifurcation region the chances of the physical occurrence of cavitation and shock waves are very high because of the off-designed CD nozzle-shaped-channel flow in blood vessels.…”
Section: Backgroundsmentioning
confidence: 99%
“…Authors [1,[5][6][7][8][9][10] reported that at the LCHI, the blood vessel with bifurcation and without any plaque and stent could experience the Sanal flow choking due to the blockage factor ( Figure 2f) leading to asymptomatic hemorrhage/stroke as a consequence of the transient pressure overshoot as a result of the shock wave generation. [6] The research findings of the authors corroborated that, [1,6] at the Sanal flow choking condition, when the BPR reaches the LCHI anywhere in the circulatory circuit with sudden expansion or bifurcation region the chances of the physical occurrence of cavitation and shock waves are very high because of the off-designed CD nozzle-shaped-channel flow in blood vessels. Certainly, the Sanal flow choking is more severe near the heart valves, which create a CD nozzle flow effect leading to cavitation due to the geometrical shape or orientation of leaflets or cusps.…”
Section: Backgroundsmentioning
confidence: 99%
See 3 more Smart Citations